Sustainable Homes for All: Mass Timber Construction - Prem, Architect Bharathi (Current Approaches in Engineering Research and Technology Vol. 2, 2024)
With the explosion in increased population migrating to cities, housing infrastructure poses one of the biggest challenges in India as well as other countries. The need for a safe space to live which transforms the quality and well-being reducing environmental challenges is a necessity. This article advocates for a paradigm shift in construction methodologies, emphasizing the adoption of emerging technologies to build faster while delivering superior quality homes at an economically viable scale. Central to this transformation is the utilization of Mass Timber Construction within a sustainable construction framework. By harnessing the potential of mass timber technology, we aim to mitigate the environmental impact of traditional construction practices and usher in a new era of carbon-neutral buildings and faster construction.